2005
DOI: 10.1091/mbc.e04-08-0689
|View full text |Cite
|
Sign up to set email alerts
|

p53 C-Terminal Phosphorylation by CHK1 and CHK2 Participates in the Regulation of DNA-Damage-induced C-Terminal Acetylation

Abstract: The tumor suppressor protein p53 mediates stress-induced growth arrest or apoptosis and plays a major role in safeguarding genome integrity. In response to DNA damage, p53 can be modified at multiple sites by phosphorylation and acetylation. We report on the characterization of p53 C-terminal phosphorylation by CHK1 and CHK2, two serine/ threonine (Ser/Thr) protein kinases, previously implicated in the phosphorylation of the p53 N terminus. Using tryptic phosphopeptide mapping, we have identified six additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
151
0
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(160 citation statements)
references
References 52 publications
5
151
0
4
Order By: Relevance
“…To further investigate the phosphorylation of serines 362 and 366 by IKK2 in vivo, we treated mouse embryonic fibroblast (MEF) cells expressing WT or AA mutant p53 with doxorubicin, and then immunoprecipitated the phosphorylated p53 proteins with antibody to phos-Ser-366 p53 (18) and immunoblotted them with p53 antibody. MEF cells infected with the lentiviral vector making p53 WT induced phosphorylation on doxorubicin treatment ( (Fig.…”
Section: Ikk2 Phosphorylates P53mentioning
confidence: 99%
“…To further investigate the phosphorylation of serines 362 and 366 by IKK2 in vivo, we treated mouse embryonic fibroblast (MEF) cells expressing WT or AA mutant p53 with doxorubicin, and then immunoprecipitated the phosphorylated p53 proteins with antibody to phos-Ser-366 p53 (18) and immunoblotted them with p53 antibody. MEF cells infected with the lentiviral vector making p53 WT induced phosphorylation on doxorubicin treatment ( (Fig.…”
Section: Ikk2 Phosphorylates P53mentioning
confidence: 99%
“…It is well known that in certain cases a stress-induced increase in p53 activity comes from a phosphorylation-acetylation cascade (12,16,43,63,66). There thus is a possibility that depsipeptide activates kinases and thereafter induces p53 acetylation in a postphosphorylation pattern.…”
Section: P53 Acetylation At K373/k382 Is Required For Depsipeptideindmentioning
confidence: 99%
“…In addition, phosphorylation of p53 at the Ser20 or Thr18 site plays a critical role in stabilizing the p300-p53 complex (12,53), and phosphorylation of p53 at Ser15 increases binding to CBP (43) and p300 (16). Recently, it was reported that p53 C-terminal phosphorylation induced by CHK1 and CHK2 also modulates Cterminal acetylation in responding to DNA damage (63). These data indicate that p53 modulation is a complex process, and the biological consequences of p53 activation induced by certain stimuli may be dependent on p53 posttranslational modifications at multiple sites.…”
mentioning
confidence: 99%
“…However, at least one of the amino acids present in p53⌬24 and not in p53⌬30 has been shown to be post-translationally modified. Serine 366 is in fact one of several residues phosphorylated by CHK2 after DNA damage, a modification that seemed only required for the activation of a subset of p53 target genes (46). Nevertheless, in all of the reports cited above, p53⌬30 seems to behave like p53⌬24, and in both cases, the p53 CTD serves as a positive regulator for p53 functions.…”
Section: Discussionmentioning
confidence: 98%